Struktur dan Fungsi Sosial Nyanyian Rakyat Tale di Sebukar Kecamatan Tanah Cogok Kabupaten Kerinci - Nabila Paramita; Zulfadhli Zulfadhli (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Folk songs have various forms, one of which is tale which comes from the word monotheism which means to unite God. This tale is made a tradition and sung to release the departure of pilgrims. Over time, the tale song seems almost extinct because the younger generation of the Sebukar area, Tanah Cogok District, Kerinci Regency, has not been able to preserve it. This study aims to describe the social structure and function of the tale of departure folk song in Sebukar, Tanah Cogok District, Kerinci Regency. This research uses the type of literary-qualitative research and descriptive method. recording of tale folk songs, and data collection are techniques used in collecting data from local informants. Data analysis techniques in this study are the stages of classification, discussion, conclusion and reporting. The research findings include the structure of the folk song of the tale in Sebukar Kecamantan Tanah Cogok, Kerinci Regency, namely (1) the physical structure in the form of lines, stanzas, diction, and sound, (2) the inner structure in the form of themes, feelings, tones, and mandates. Then the social function of the folk song of the tale in Sebukar, Tanah Cogok District, Kerinci Regency, namely a means of entertainment, hope and prayer, a tool of da'wah, and an heir of oral tradition.